Analisis Terhadap Putusan Pengadilan Dalam Perkara Perdata Yang Hukumnya Tidak Ada Atau Hukumnya Tidak Jelas - Ning Adiasih (Jurnal Hukum PRIORIS, 2017)
In practice, there will be events which were not regulated by was Laws, or even if it was regulated, still unclear or incomplete. Therefore, a Judge is responsible to fulfill the absence of law by creating, complete or clarify the law it if it needs to be created, completed or clarified by finding the law through exploration and understanding legal norms and justice which lives inside the society so that the law will be applied to the particular event. To provide justice, a Judge should seek the truth behind any event which proceed upon him/her by examining an event and connect it with the governing law and provide a Judgment by stating the law for the particular event. This research is using normative legal research by researching literature and supported by data from interview both from practitioner and academician. The specification of this research is descriptive analytic, and the data compiled is analyze qualitatively towards the substance of legal finding. Good law is law which was accordingly with the living law in society and a reflection of the governing norms in the society. In reality, lawmakers only enacted general law whereas consideration on concrete issues is given to Judges. The background for this is that lawmakers are not fully aware of the newest social norms therefore a Judge must complete the written laws or create a new law by establishing law (rechtsvorming) and finding the law (rechtsvinding) to filled out the absence of law and avoid cases not being examined in the court of law with reason that the written law is unclear or no written law was enacted in concrete cases. Judgments which are taken by Judges have to be accountable with their conscience.